Preparation and Characteristics of NLC Coenzym Q10 with A Combination of Hyaluronic Acid - Nurhidayah Sarifuddin; Widji Soerarti; Noorma Rosita (Health Notions, 2019)
Coenzyme Q10, often also known as ubiquinone, coenzyme Q10 or Q10, is soluble in lipids and is naturally present in plants, animals and in mitochondria. Coenzyme Q10 functions as an antioxidant that can protect the body from damage caused by free radicals. Hyaluronic acid is known as a hydrophilic polymer derived from polysaccharides which has the ability to increase percutaneous penetration by changing the composition of tightly arranged stratum corneum cells to increase the permeability of the skin. Nanostructured Lipid Carrier is a modification of the SLN system, consisting of a mixture of solid and liquid lipids (oil), stabilized by aqueous surfactant solution, is one method to increase drug penetration through the stratum corneum because it has several advantages. The purpose of this study was to see the effect of adding hyaluronic acid to the characteristics of the Nanostructure Lipid Carrier (NLC) as anti aging. Examination of characteristics including organoletis, pH, particle size and polidispersity index was carried out. The results of organoleptic NLC coenzym Q10-HA examination obtained dark orange color, liquid consistency, lipid efficacy odor and soft texture. The pH measurement results of the preparation ranged from 5.05-5.23. The results of the particle size examination ranged from 267-128 nm and the particle size distribution ranged between 0.308-0.200 Keywords: Coenzym Q10, Hyaluronic acid , NLC